Peran Surat Kabar Kampus Ganto sebagai Media Informasi pada Pemilu BEM UNP Tahun 2026 - Winni Ahatri; Rahmadhona Fitri Helmi (YASIN, 2026)
Although the press holds an important position in the democratic order and has been widely studied, research specifically examining the role of the student press in providing political information within higher education institutions remains limited. This study aimed to analyse the role of Surat Kabar Kampus (SKK) Ganto as a Student Press Organization (LPM) and an information medium in the Student Executive Board General Election (Pemilu BEM) at Universitas Negeri Padang (UNP), as well as to identify the internal and external constraints encountered in performing this role. This study employed a qualitative approach. Data were collected through in-depth interviews with seven categories of informants selected using purposive sampling combined with snowball sampling. The results showed that the role of SKK Ganto as an information medium in the Pemilu BEM had not been optimal. Of the three press functions examined, the information and educational functions had not been fully implemented, whereas the social control function had begun to be performed; however, SKK Ganto still tended to be less proactive in reporting issues related to the Pemilu BEM. The performance of this role also faced significant challenges originating from both within the organization and the external environment. These findings confirm that SKK Ganto needs to strengthen the implementation of its information, educational, and social control functions and conduct more comprehensive performance evaluations and organizational development. This study provides a practical contribution to strengthening the role of the student press as a medium of political information within the university environment and expands research on the student press, student organizations, and the dynamics of politics and democracy in higher education institutions.